Roles of Macrophage Subtypes in Bowel Anastomotic Healing and Anastomotic Leakage - Jinyao Shi; Zhouqiao Wu; Ziyu Li; Jiafu Ji (Journal of Immunology Research)
Macrophages play an important role in host defense, in addition to the powerful ability to phagocytose pathogens or foreign matters. They fulfill a variety of roles in immune regulation, wound healing, and tissue homeostasis preservation. Macrophages are characterized by high heterogeneity, which can polarize into at least two major extremes, M1-type macrophages (classical activation) which are normally derived from monocytes and M2-type macrophages (alternative activation) which are mostly those tissue-resident macrophages. Based on the wound healing process in skin, the previous studies have documented how these different subtypes of macrophages participate in tissue repair and remodeling, while the mechanism of macrophages in bowel anastomotic healing has not yet been established. This review summarizes the currently available evidence regarding the different roles of polarized macrophages in the physiological course of anastomotic healing and their pathological roles in anastomotic leakage, the most dangerous complication after gastrointestinal surgery.